2007
DOI: 10.1016/j.jdermsci.2007.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Topical application of laminin-332 to diabetic mouse wounds

Abstract: Background-Keratinocyte migration is essential for wound healing and diabetic wound keratinocytes migrate poorly. Keratinocyte migration and anchorage appears to be mediated by laminin-332 (LM-332). Impaired diabetic wound healing may be due to defective LM-332 mediated keratinocyte migration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 47 publications
(56 reference statements)
2
9
0
1
Order By: Relevance
“…Both phenomena contributed to protracted re-epithelialization of COL7A1-deficient skin wounds, but aberrant laminin-332 organization is likely to be the main cause. Laminin-332 is commonly believed to be a promoter of epithelialization during wound healing (30)(31)(32), despite some controversy in the literature (33,34). Here, we found that irregular deposition of laminin-332 was associated with delayed migration of the epidermal tongues in the absence of COL7A1 in vivo, which indicates that not the sheer presence of laminin-332, but its assembly and deposition, play a functional role.…”
Section: Discussionmentioning
confidence: 57%
“…Both phenomena contributed to protracted re-epithelialization of COL7A1-deficient skin wounds, but aberrant laminin-332 organization is likely to be the main cause. Laminin-332 is commonly believed to be a promoter of epithelialization during wound healing (30)(31)(32), despite some controversy in the literature (33,34). Here, we found that irregular deposition of laminin-332 was associated with delayed migration of the epidermal tongues in the absence of COL7A1 in vivo, which indicates that not the sheer presence of laminin-332, but its assembly and deposition, play a functional role.…”
Section: Discussionmentioning
confidence: 57%
“…Wounds from individual mice were digitally photographed daily for 7 d. All photographs were taken from an angle perpendicular to the wound with a sterile ruler placed adjacent to the wounds for standardization (7). The wound area was quantified using NIH ImageJ software (NIH, Bethesda, MD, USA); and wound closure was expressed as the ratio of actual wound area to initial wound size.…”
Section: Quantification Of Wound Closurementioning
confidence: 99%
“…Extracellular matrix (ECM) is known to play a critical role in tissue repair, serving as a scaffold and as a modulator of cell function and growth factor functionality. 21,22 Cells cultured in adherent monolayers ultimately need to be lifted into suspension for further handling=manipulation, but this process disrupts any ECM milieu that may have been established. Therefore, we also hypothesize that ASCs prepared and delivered as 3D multicellular aggregates (MAs) will exhibit enhanced biological and therapeutic properties compared to cells prepared using traditional monolayer techniques and delivered as cell suspensions.…”
Section: Introductionmentioning
confidence: 99%